Influence of chorionicity on healthy twin pregnancy outcome - Akšam, Slavica; Plešinac, Snežana; Dotlić, Jelena; Kocijančić Belović, Dušica; Marjanović Cvjetićanin, Mirjana (Vojnosanitetski pregled, 2021)
Background/Aim. It is still under debate in what sense and extent can chorionicity impact the pregnancy outcome of twins without gestational complications specific for monochorionicity. The study aimed to evaluate the effect of chorionicity on healthy twin pregnancy outcome. Methods. The study included patients with uncomplicated twin pregnancies after first trimester that were checked-up and delivered at the Clinic of Obstetrics and Gynecology, Clinical Center of Serbia, Belgrade during three years (2010–2013). Data regarding mother’s age, comorbidities, parity, presence and type of gestational complications, chorionicity, mode and time of pregnancy ending, birth-weight and Apgar score of twins were determined. Obtained data were compared and statistically analyzed. Results. The study included 361 women with mean age of 33 years. Regardless of chorionicity, twins were mostly born during the 36th gestational week and received Apgar score ≥ 8. Only three monochorionic twins were stillborn, two preterm (29 and 32 gestational week) and one in term (35 gestational week) delivery. Contrary, no intrauterine fetal deaths were recorded. Monochorionicity negatively correlated with having live-born twins (OR = 0.023; CI = [0.001–0.609]; p = 0.024), but was not associated with twins condition at birth, i.e. Apgar score (p = 0.345), pregnancy ending time (p = 0.578) or any other twins characteristic. However, premature preterm membrane rupture and earlier gestational week of pregnancy ending were important confounding factors for relationship between chorionicity and pregnancy outcome. Conclusion. Monochorionicity increases risk for adverse pregnancy outcomes even for uncomplicated, healthy twin pregnancy, but has no influence on the condition of twins who survive until term. If appropriate surveillance and therapy are applied, both healthy twins can be delivered at term regardless of chorionicity.